Clonality Analysis of Helicobacter pylori in Patients Isolated from Several Biopsy Specimens and Gastric Juice in a Japanese Urban Population by Random Amplified Polymorphic DNA Fingerprinting. (17th November 2013) - Toita, Nariaki; Yokota, Shin-ichi; Fujii, Nobuhiro; Konno, Mutsuko
Abstract : Background . The number of Helicobacter pylori clones infecting a single host has been discussed in numerous reports. The number has been suggested to vary depending on the regions in the world. Aim . The purpose of this study was to examine the number of clones infecting a single host in a Japanese urban population. Materials and Methods . Thirty-one Japanese patients undergoing upper gastrointestinal endoscopy were enrolled in this study. H. pylori isolates (total 104 strains) were obtained from biopsy specimens (antrum, corpus, and duodenum) and gastric juice. Clonal diversity was examined by the random amplified polymorphic DNA (RAPD) fingerprinting method. Results . The RAPD fingerprinting patterns of isolates from each patient were identical or very similar. And the isolates obtained from several patients with 5- to 9-year intervals showed identical or very similar RAPD patterns. Conclusion . Each Japanese individual of an urban population is predominantly infected with a single H. pylori clone.